Activating creativity in business organizations through the introduction of empowerment - chetatha, Aicha (Dirassat Journal Economic Issue, 2013)
The Term of empowerment is One of the Modern Terms; It was appear in the dictionary of the U.S. administration "Empowerment", Where it occupies this procedure or method in the management of human resources great importance in particular; if you think about the organization in the application of total quality management, and in general it Has an important role in the success organizations Which destined for to the customer, It helps to creativity and innovation among individuals, and also to shorten the times such as: production period and the duration of decision-making, so there believes that empowerment employees in organizations which focuses on the customer is is essential for individuals dealing directly with customers in order to enable them to make all the decisions necessary in dealing with customers.